Test article for checking JATS in Janeway (Ergo, An Open Access Journal of Philosophy)
Note that the HTML page displays Article Title, Authors, Abstract, and Keywords from the Janeway metadata, not the JATS XML. Thus, please do not be concerned when you see that these front matter fields do not match what you have tagged in the JATS.